'A tale of two cases:' The health, illness, and physical activity stories of two children living with cystic fibrosis. (January 2014) - Moola, Fiona J; Faulkner, Guy EJ
Storytelling is perennial, and central to the human condition. Although illness may shatter identity and one's role and place in the broader social world, narrative may aid in the process of self-reparation. Despite the merits of the narrative approach, it has been underutilized with children who are living with cystic fibrosis (CF). The role that illness narratives may play in influencing CF youths' physical activity also remains poorly investigated. This article drew on the qualitative case study methodological tradition to narrate the stories of two children living with CF at a children's hospital in Canada. The findings beg researchers to consider (a) how children with life-limiting diseases borrow multiple illness narrative types, (b) the role of development in influencing the kinds of stories that children can tell, and (c) the impact of illness narratives on physical activity. By rendering the tales of two CF youth in this study, we respond to Aurthur Frank's call; taking a multiple narrative turn, we listen to stories of a different kind of suffering.